The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.3390/rs4010111
|View full text |Cite
|
Sign up to set email alerts
|

Beyond Range: Innovating Fluorescence Microscopy

Abstract: Time-of-Flight (ToF) technologies are developed mainly for range estimations in industrial applications or consumer products. Recently, it was realized that ToF sensors could also be used for the detection of fluorescence and of the minute changes in the nanosecond-lived electronic states of fluorescent molecules. This capability can be exploited to report on the biochemical processes occurring within living organisms. ToF technologies, therefore, provide new opportunities in molecular and cell biology, diagno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 40 publications
0
15
0
Order By: Relevance
“…In the last decade a number of SPAD array image sensors have emerged, which simultaneously deliver single photon sensitivity, megapixel spatial resolution and picosecond timing resolution [7][8][9]. These SPAD arrays hold great promise for the advancement of time-resolved fluorescence microscopy, but they currently have a low fill factor and much higher noise levels than MCP-based detectors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the last decade a number of SPAD array image sensors have emerged, which simultaneously deliver single photon sensitivity, megapixel spatial resolution and picosecond timing resolution [7][8][9]. These SPAD arrays hold great promise for the advancement of time-resolved fluorescence microscopy, but they currently have a low fill factor and much higher noise levels than MCP-based detectors.…”
Section: Discussionmentioning
confidence: 99%
“…However, direct detection of individual photons is not possible with these particular cameras. In this context, we note CMOS single photon avalanche diode (SPAD) array image sensors have been developed, incorporating picosecond timing circuitry in each pixel or chip [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…The pixel integrates both phases of the modulated fluorescence simultaneously by directing accumulated photocharge via dual transfer gates from the photogate to storage gates. The operating principle of this imager is very similar to that of various time-of-flight image sensors which have been demonstrated in CMOS implementations (Kawahito et al, 2007;Lange and Seitz, 2001;Oggier et al, 2004) and demonstrated to be suitable for FLIM (Esposito, 2012).…”
Section: Spad Arraysmentioning
confidence: 91%
“…Although many FLIM experiments are performed by photoelectronic vacuum tube or image intensifier-based technology, and this technology continues to be developed (Hirvonen et al, 2014a,b;Rinnenthal et al, 2013;Sergent et al, 2010), in the last decade a number of complementary metal oxide semiconductor (CMOS) or CCD image sensors have emerged, which simultaneously deliver single photon sensitivity, megapixel spatial resolution and picosecond timing resolution (Esposito, 2012). While solid state detector arrays have been used for frequency-domain FLIM (Esposito, 2012), the recent development of single-photon avalanche diode (SPAD) array detectors with picosecond timing capabilities hold great promise for the advancement of time-resolved fluorescence microscopy -especially in view of the limitations of the variety of current FLIM implementations (Charbon et al, 2013;Charbon, 2014).…”
Section: Detector Developmentsmentioning
confidence: 99%
See 1 more Smart Citation